Endocrine responses and acute mTOR pathway phosphorylation to resistance exercise with leucine and whey - Lane, MT; Herda, TJ; Fry, AC; Cooper, MA; Andre, MJ; Gallagher, PM (Biology of Sport, 2017)
Leucine ingestion reportedly activates the mTOR pathway in skeletal muscle, contributing to a hypertrophy response. The purpose of the study was to compare the post-resistance exercise effects of leucine and whey protein supplementation on endocrine responses and muscle mTOR pathway phosphorylation. On visit 1, subjects (X±SD; n=20; age=27.8±2.8yrs) provided baseline blood samples for analysis of cortisol, glucose and insulin; a muscle biopsy of the vastus lateralis muscle to assess mTOR signaling pathway phosphorylation; and were tested for maximum strength on the leg press and leg extension exercises. For visits 2 and 3, subjects were randomized in a double-blind crossover design to ingest either leucine and whey protein (10g+10g; supplement) or a non-caloric placebo. During these visits, 5 sets of 10 repetitions were performed on both exercises, immediately followed by ingestion of the supplement or placebo. Blood was sampled 30 min post-, and a muscle biopsy 45 min post-exercise. Western blots quantified total and phosphorylated proteins. Insulin increased (α<.05) with supplementation with no change in glucose compared to placebo. Relative phosphorylation of AKT and rpS6 were greater with leucine and whey supplementation compared to placebo. Supplementation of leucine and whey protein immediately after heavy resistance exercise increases anabolic signaling in human skeletal muscle.